The forts of Mahdia remaining on the banks of the Nile Omdurman……case studyطوابي المهدية الباقية على ضفتي نيل أم درمان دراسة حالة - Dr.Asmaa Mohammed Ismail (Journal of General Union of Arab Archaeologists, 2019)
Abstract: The period of revolution and the state of Mahdia is an important period in the history of modern Sudan, which has lived most of its history in wars and military conflicts, especially internal and external against the rule of Turkey, Egypt or English-Egyptian, and therefore formed defensive fortifications Al-Tawabi is the outstanding symbol of the historical remains of the Caliph Abdullah and his leaders on the banks of the Nile to defend his capital, Omdurman. The research aimed at studying the construction sites, construction methods, construction materials, its current status and the extent to which it achieved the military balance and the combat equation in the wars of Mahdia against the British The study concluded that Al-Tawabi is one of types of stonemasons are fast-built. The study concluded that this type of defense buffer is weak in reaching the set of objectives to be reached from its construction, its complexity and the efficiency of the weapons of the era in which it was established تمثل فترة ثورة ودولة المهدية فترة مهمة في تاريخ السودان الحديث، والتي عاشت معظم فترات تاريخها في حروب وصراعات عسكرية خاصة داخلية وخارجية ضد الحكم التركي المصري أو الإنجليزي المصري، لذلك شكلت التحصينات الدفاعية ـ الطوابي ـ العلامة البارزة من الآثار الباقية لتلك الحقبة التاريخية التي قام بها الخليفة عبدالله وقواده على ضفتي النيل للدفاع عن عاصمته مدينة أم درمان، واستهدف البحث دراستها من حيث أماكن تشيدها وأسلوب التشييد، ومواد البناء، وعددها عند التشييد، وما تبقى منها حتى الآن، وحالتها الراهنة، ومدى تحقيقها للموازنة العسكرية والمعادلة القتالية في حروب المهدية ضد الإنجليز، وخلصت الدراسة إلى أن الطوابي من أنواع الاستحكامات سريعة التشييد، واستنتجت الدراسة مدى ضعف هذه النوعية من الاستحكامات الدفاعية في الوصول إلى مجموعة الأهداف المراد الوصول إليها من تشييدها، ومواكبتها ومدى كفاءتها لأسلحة العصر الذي أنشئت فيه .